PARP15 Is a Susceptibility Locus for Clarkson Disease (Monoclonal Gammopathy-Associated Systemic Capillary Leak Syndrome) - Chan, Eunice C; Ablooglu, Ararat J; Ghosh, Chandra C; Desai, Abhishek; Schaible, Niccole; Chen, Xiuying; Zhao, Ming; Olano, M Renee; Ganesan, Sundar; Lack, Justin B; Krishnan, Ramaswamy; Parikh, Samir M; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2024)
Vascular leakage is a deadly complication of severe infections, ranging from bacterial sepsis to malaria. Worldwide, septicemia is among the top 10 causes of lethality because of the shock and multiorgan dysfunction that arise from the host vascular response. In the monoclonal gammopathy-associated capillary leak syndrome (MG-CLS), even otherwise mundane infections induce recurrent septic-like episodes of profound microvascular hyperpermeability and shock. There are no defined genetic risk factors for MG-CLS or effective treatments for acute crises. We characterized predicted loss-of-function mutations in PARP15 (poly[ADP-ribose] polymerase 15), a protein of unknown function that is absent in mice, in patients with MG-CLS. We analyzed barrier function in PARP15-deficient vascular endothelial cells and vascular leakage in mice engineered to express wild-type or loss-of-function variant human PARP15. We discovered several loss-of-function PARP15 variants associated with MG-CLS. These mutations severely reduced PARP15 enzymatic function. The presence of the most frequently detected variant (G628R) correlated with clinical markers of severe vascular leakage. In human microvascular endothelial cells, PARP15 suppressed cytokine-induced barrier disruption by ADP-ribosylating the scaffold protein JIP3 (c-Jun N-terminal kinase-interacting protein 3) and inhibiting p38 MAP (mitogen-activated protein) kinase activation. Mice expressing enzymatically inactive human PARP15(G628R) were significantly more prone to inflammation-associated vascular leakage than mice expressing wild-type PARP15 in a p38-dependent fashion. represents a previously unrecognized genetic susceptibility factor for MG-CLS. PARP15-mediated ADP ribosylation is an essential and genetically determined mechanism of the human vascular response to inflammation.